2009
DOI: 10.1002/path.2512
|View full text |Cite
|
Sign up to set email alerts
|

Parkin regulates paclitaxel sensitivity in breast cancer via a microtubule‐dependent mechanism

Abstract: Parkin is an E3 ubiquitin ligase encoded by the Parkin gene (also called PARK2, located at 6q25.2-q27) and is involved in the pathogenesis of Parkinson's disease and the development of cancer. Recently, Parkin has been demonstrated to interact with the microtubule cytoskeleton. However, the biological implication of the Parkin-microtubule axis has been poorly explored. In this study, we report for the first time that Parkin modulates sensitivity of the chemotherapeutic agent paclitaxel in breast cancer, via a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…Wang et al 33 demonstrated that parkin promoted the activity of paclitaxel to trigger multinucleation and apoptosis, rendering breast cancer cells more sensitive to this drug. Another study reported that a p53 fusion protein TAT-ODD-p53 had a significant and preferential radiosensitizing effect on hypoxic breast cancer cells by inhibiting parkin-mediated mitophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 33 demonstrated that parkin promoted the activity of paclitaxel to trigger multinucleation and apoptosis, rendering breast cancer cells more sensitive to this drug. Another study reported that a p53 fusion protein TAT-ODD-p53 had a significant and preferential radiosensitizing effect on hypoxic breast cancer cells by inhibiting parkin-mediated mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…33 Briefly, human tissue sections were stained for the expression of parkin (1:100; Abcam, UK) and detected by streptavidin-biotin-horseradish peroxidase complex formation. Tumor sections that were stained by isotype-matched immunoglobulin G instead of primary antibodies were used as a negative control.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…Many reports have suggested that parkin overexpression results in inhibition of cancer cell growth [4e6]. In the breast cancer cell line MCF7, parkin stabilizes microtubules, increases sensitivity to anti-cancer agents, and induces growth arrest [10]. There is evidence that parkin can also affect energy metabolism, namely the Warburg effect, leading to suppression of tumorigenesis in lung cancer and colon cancer cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…These studies attracted interest in studying the mechanisms by which parkin acts as a tumor suppressor. In breast cancer, parkin stabilizes microtubules and increases susceptibility to anti-cancer agents (13). In the breast cancer cell line MCF7, parkin reduces cell growth by inducing expression of cyclin-dependent kinase 6 (CDK6) (8).…”
Section: Introductionmentioning
confidence: 99%